Exploring collaborative pianist’s perceptions on benefits of acquiring conducting skills in Guangdong, China / Xu Ertong - Xu , Ertong (2025)
This study explores collaborative pianists’ perceptions of the benefits of acquiring conducting skills, focusing on three areas: auditory discrimination, orchestration, and interpersonal skills. Grounded in a conceptual framework that integrates theories of skill transfer and professional development in music, it examines how conducting training enhances technical, analytical, and social competencies in collaborative pianists. This study employs qualitative methods, combining thematic analysis of semi-structured interviews with professional pianists and content analysis of relevant literature. The findings reveal that auditory discrimination, enhanced through conducting training, helps pianists address complex musical issues such as intonation, balance, and timbre. Orchestration skills, rooted in advanced musical analysis, were found to enrich pianists’ artistic interpretation and decision-making in ensemble settings. Additionally, the study highlights the importance of interpersonal skills, such as leadership, teamwork, and empathy, which conducting training fosters and which are crucial for effective collaboration. This research highlights the interdisciplinary value of conducting skills in collaborative piano practice and their potential to foster professional development.